Explosive Volcanism of Kamchatka - IVANOV Victor; TANIGUCHI Hiromitsu; DVIGALO Victor; GOTO Akio (東北大学東北アジア研究センター, 2000)
This manuscript is a review of a great number of publications devoting to the explosive volcanism of Kamchatka (Russia), both modern and Quaternary. Detailed data on different fields of investigations are presented. The data on the main volcanic zones, their productivity, areas covered with Quaternary volcanic deposits, hazard for population and economy are discussed. Peculiarities of volcanic belts, main tectonic conceptions on origin of the Kamchatka volcanism, association with seismicity are reviewed. Volcanic production rate of Kamchatka is estimated and compared with that of Japan and the other areas of the world. We also give main quantitative parameters of active volcanoes, calderas and big explosive craters, particularly historic ones. We present data on the strong explosive eruptions in the last 10 years, including paroxysmal eruption of the Klyuchevskoy volcano of 1994. We describe the growth of huge andesitic lava domes in the Shiveluch and Bezymianny volcanoes. Information on a unique phenomenon - simultaneous eruption started in 1996 in the Karymsky volcanic center is cited. One of these eruptions happened in the old caldera filled with a deep lake and caused an ecological catastrophe in the lake. 論文 Article